Isoflavones and Bioactivities in Over-fermented Tempeh Extracts - Hanifah Nuryani Lioe; Anastasia Fitria Devi; Dian Muzdalifah; Zatil Afrah Athaillah; Nina Artanti (Jurnal Kimia Sains dan Aplikasi, 2021)
Tempeh is nutritious food prepared through solid-state fermentation of cooked and dehulled soybeans with Rhizopus sp. for about 48 h. Fermentation beyond 48 h resulted in over-fermented tempeh. There may or may not have been similar research done before, especially related to its antioxidant and cytotoxicity. This study aims to determine the characteristics of fermented tempeh for up to 156 h. Samples were fermented at 0, 24, 48, 60, 72, 84, 96, 108, 120, and 156 h. Samples were dried, grounded, and extracted with acetone, followed by defatting with n‑hexane. Extracts were dissolved in organic solvents for free radical scavenging activity (FRSA) and cytotoxicity assays. The 120-h tempeh extract, at the concentration of 1,000 μg/mL, demonstrated the highest FRSA (81.31% inhibition) against 100 µM 2,2-diphenyl-1-picrylhydrazyl (DPPH) solution. Meanwhile, the 108-h tempeh extract at 1,000 μg/mL possessed the highest cytotoxicity (IC50 of 2.54 μg/mL) against MCF-7 breast cancer cell lines. Liquid Chromatography-Mass Spectrometry/Mass Spectroscopy (LC-MS/MS) analysis revealed the presence of daidzin, genistin, daidzein, and genistein in all extracts. Extracts prepared from 108 h and 120 h tempeh stood out from other extracts in the Partial Least Square (PLS) bi-plot due to their high percentage of inhibition, low response of daidzin, and high responses of the other three isoflavones. The cytotoxicity assays of the standard isoflavones showed that genistein had the lowest IC50 value at 4.82 ± 0.11 μg/mL. Standard genistein showed a low percentage of inhibition at 29.79 ± 9.10.